MODELS AND METHODS OF DESIGNING THE ORGANIZATIONAL STRUCTURE OF A VIRTUAL TEAM - Kovalchuk, Oleh; Zachko, Oleh; Kobylkin, Dmytro (Management of Development of Complex Systems, 2022)
The modern organizational system is constantly exposed to the turbulent internal and external environment. To ensure the effective implementation of projects, programs and project portfolios, the activities of all human resources should be rationally coordinated. The use of information systems for the management of the organization's activities is a rational toolkit for the implementation of such tasks. To develop this information system, organizational structures should be analyzed in order to develop a model of an information analytical system to support personnel decision-making. The positive and negative sides of various organizational structures of organizations are considered. The subject of the study is resource management in projects of safety-oriented systems. Management of human resource management projects and programs in the civil defense system. The purpose of the article is to improve the efficiency of human resources management of the civil defense system of Ukraine. Research methods: the method of analyzing hierarchies, graphodynamic theory, empirical research, analysis and synthesis. The following results were obtained: It is proposed to use the graphical form of presentation of organizational models that belong to safety-oriented systems. Conclusions: A model of a multi-agent information system has been developed. To solve the task of finding the optimal organizational structure, an efficiency criterion has been defined, according to which a comparative analysis of organizational structures will be carried out, and such a criterion can be the manager's expenses for the formation of a project team. Therefore, the formation of virtual teams allows you to effectively manage the human resources of the project. They are formed from a group of applicants who are united by a common goal. In the project team where a temporary virtual organization is formed, it is allowed to use special expert knowledge and at the same time the experts do not cross each other. Also, this format allows you to form teams that have geographic restrictions and at the same time save resources.